Profitability of the lamb fattening housing on raised pens and at ground level in the southeast of Mexico - Muñoz-Osorio, Germani Adrián (2022)
The aim of this study was to compare the profitability of fattening lambs under two types of housing in the subhumid tropics of Mexico. Data on production parameters and production costs of 32 lambs, 16 housed in raised pens and 16 in pens at ground level, were analysed to determine the cost-benefit relationship and profitability. The cost-benefit ratio and the profitability of fattening lambs in raised pens were superior compared to fattening lambs in pens at ground.